2016
DOI: 10.12688/f1000research.8004.1
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-renal syndrome

Abstract: Cardio-renal syndrome is a commonly encountered problem in clinical practice. Its pathogenesis is not fully understood. The purpose of this article is to highlight the interaction between the cardiovascular system and the renal system and how their interaction results in the complex syndrome of cardio-renal dysfunction. Additionally, we outline the available therapeutic strategies to manage this complex syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 64 publications
0
44
0
Order By: Relevance
“…The complete shutdown of vitamin D synthesis would consequently enhance an uncontrolled reaction over accumulation of Ang-II that, in turn, scatters the high viability of pro-inflammatory cytokine and interleukins, such as IL-6, followed by a sudden regression of kidney, heart, and lung axis functionality (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete shutdown of vitamin D synthesis would consequently enhance an uncontrolled reaction over accumulation of Ang-II that, in turn, scatters the high viability of pro-inflammatory cytokine and interleukins, such as IL-6, followed by a sudden regression of kidney, heart, and lung axis functionality (7).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology that underlies the complex loop of lungheart-kidney interactions is a well-accepted assumption, a kind of respiratory-cardio-renal syndrome condition that gives rise to a susceptibility to many primary and secondary dysfunctions, such as infections, auto-immune reactions, sepsis, and declined endocrine activity (low level of erythropoietin (EPO)). In COVID-19 patients, there is often seen a long-term clinical history of kidney/heart deficit advocated by a compromised renin angiotensin system (RAS) [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…CKD is also an independent risk factor for CVD [7] and CVD progression directly contributes to kidney function decline [8]. These multiple interactions between the heart and kidneys have led to the concept of the cardiorenal syndrome (CRS), in which acute or chronic dysfunction of either the heart or the kidneys leads to dysfunction of the other organ [9,10]. The molecular mechanisms underlying these interactions remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…When using the TAC model to study heart failure it is important to take the cardiorenal axis into account, patients with reduced cardiac function often also experience CKD ( Harada et al, 2018 ; Kumar and Seth, 2019 ; Patel et al, 2019 ; Zaleska-Kociecka et al, 2019 ), as it has been suggested that a decline in kidney function directly contributes to further deterioration of cardiac function in patients ( Hewitson et al, 2015 ; Gnanaraj and Radhakrishnan, 2016 ). Several papers have indicated that a good animal model that properly represents the clinical manifests of CRS is lacking ( Szymanski et al, 2012 ; Tan et al, 2018 ; Liu, 2019 ).…”
Section: Discussionmentioning
confidence: 99%